Optimization of novel nanocomposite powder for simultaneous removal of heavy metals from palm oil mill efuent (POME) by response surface methodology (RSM) - Anthonette, James; Md Rezaur, Rahman; Durul, Huda; Mohammed M., Rahman; Jamal, Uddin; Muhammad Khusairy, Bakri; Avishek, Chanda (Springer Nature, 2024)
The treatment of palm oil mill efuent (POME) via adsorption was investigated using a novel nanocomposite powder with the addition of titanium (IV) dioxide (TiO2) and montmorillonite clay (MMT). Reduced heavy metal content, turbidity, pH, chemical oxygen demand (COD), and total suspended solids (TSS) in POME supported this result. The adsorption processes were carried out in POME with pH 4.4, 658 FAU turbidity, 1256 mg/l COD, and 563 mg/l TSS at a constant mixing speed of 180 rpm for 48 h, with diferent dosages of adsorbent. The atomic adsorption spectrometry (AAS) analysis revealed that MMT clay was efective in removing lead (Pb) and zinc (Zn) by 86.7 and 97.3%, respectively, aided by the role of activated carbon and photocatalytic behavior of TiO2 to remove recalcitrant organic pollutants which result in 91.6% reduction in POME turbidity. The fnal pH value of POME was within the allowable discharged limit as stated in the Environmental Quality Act 1974 (EQA 1974). The response surface methodology (RSM) was modeled based on the COD and TSS analysis results. The fndings determined that 1wt% KOH-AC, 0.628wt% TiO2, and 2wt% MMT clay were the best composition values of novel nanocomposite in showing the most efective reduction of COD and TSS.